Exploring Critical Success Factors that Influence Tourism Success: a Qualitative Study in the Context of Diverse Tourism Destinations - Sutrisno, Wahyudhi (Politeknik Negeri Bali, 2024)
Tourism is an important industry that has a huge impact on the economy. This economic impact comes from the spending of tourists who visit a tourism destination. Therefore, tourism destinations must make the necessary arrangements to effectively receive and maximize this economic opportunity. An important step in understanding and effectively managing the tourism industry is to identify the critical aspects that contribute to its success. Examining critical success factors in various tourism destinations, taking into account geographic, cultural, and economic variations, is essential to understanding the intricacies of the tourism sector as a whole. This research utilizes a qualitative research methodology, namely content analysis, which includes conducting a literature review and using triangulation. The purpose of this study was to identify the key factors that influence the success of the tourism industry in the context of diverse tourism destinations. The research findings show that various key factors significantly influence the success of various tourism destinations. These factors are uniqueness of location, attractiveness of tourist attractions, ease of access, government support, local community involvement, availability of facilities and infrastructure, quality of human resources, effectiveness of marketing and promotion efforts, and tourist motivation. Within the realm of green tourism, these findings underscore the imperative of incorporating sustainable practices into each of these elements. This includes advocating for environmentally friendly modes of transportation, endorsing local environmentally conscious enterprises, and ensuring that tourism development amplifies rather than exploits natural and cultural resources. This integration will not only adhere to the ideals of sustainable tourism but also have the ability to boost the economic advantages of the tourism industry by attracting environmentally aware travelers.